Analysis of the Impact of Exchange Rate Fluctuations on the Profitability of Footwear Export Companies in Indonesia - Hikmah Goyatun Napilah; Dian Ramdani (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the effect of USD/IDR exchange rate fluctuations on the profitability of export-manufacturing companies in the Indonesian footwear sector, with a case study of footwear manufacturing company in Indonesia. Profitability is measured using three key indicators: Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The research uses secondary data, including company financial statements and exchange rate data from 2018 to 2023. The analytical method employed is simple linear regression. The results indicate that exchange rate fluctuations tend to negatively affect all profitability indicators. However, the influence is not statistically significant (p-value > 0.05). The coefficient of determination (R²) shows that exchange rates explain about 27% to 37% of profitability variation. Despite the lack of statistical significance, the consistently negative relationship suggests that exchange rate volatility remains a crucial risk factor for export companies reliant on imported raw materials. The study recommends implementing risk management strategies such as hedging and resource diversification to maintain financial performance stability.